Evaluation of PCR approaches for detection of Bartonella bacilliformis in blood samples - Gomes, Cláudia (2016)
Background The lack of an effective diagnostic tool for Carrion’s disease leads to misdiagnosis, wrong treatments and perpetuation of asymptomatic carriers living in endemic areas. Conventional PCR approaches have been reported as a diagnostic technique. However, the detection limit of these techniques is not clear as well as if its usefulness in low bacteriemia cases. The aim of this study was to evaluate the detection limit of 3 PCR approaches. Methodology/Principal Findings We determined the detection limit of 3 different PCR approaches: Bartonella-specific 16S rRNA, fla and its genes. We also evaluated the viability of dry blood spots to be used as a sample transport system. Our results show that 16S rRNA PCR is the approach with a lowest detection limit, 5 CFU/μL, and thus, the best diagnostic PCR tool studied. Dry blood spots diminish the sensitivity of the assay. Methodology/Principal Findings We determined the detection limit of 3 different PCR approaches: Bartonella-specific 16S rRNA, fla and its genes. We also evaluated the viability of dry blood spots to be used as a sample transport system. Our results show that 16S rRNA PCR is the approach with a lowest detection limit, 5 CFU/μL, and thus, the best diagnostic PCR tool studied. Dry blood spots diminish the sensitivity of the assay. Conclusions/Significance From the tested PCRs, the 16S rRNA PCR-approach is the best to be used in the direct blood detection of acute cases of Carrion’s disease. However its use in samples from dry blood spots results in easier management of transport samples in rural areas, a slight decrease in the sensitivity was observed. The usefulness to detect by PCR the presence of low-bacteriemic or asymptomatic carriers is doubtful, showing the need to search for new more sensible techniques.